2009
DOI: 10.1111/j.1447-0594.2009.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its relation to sociodemographic factors among elderly people living in Tehran

Abstract: Sociodemographic inequalities, smoking and having diseases should be the main targets for improving the QOL in the elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 13 publications
2
19
1
2
Order By: Relevance
“…The mean QOL scores measured in the elderly population, in other countries were much higher than the results obtained in Iran (12). The QOL subscales were influenced by different factors including age, gender, financial status and more importantly by education, financial and marital status as other studies showed (5, 13, 14). Therefore, it is important to inform the elderly population of the behavioral modifications benefits of the QOL.…”
mentioning
confidence: 74%
“…The mean QOL scores measured in the elderly population, in other countries were much higher than the results obtained in Iran (12). The QOL subscales were influenced by different factors including age, gender, financial status and more importantly by education, financial and marital status as other studies showed (5, 13, 14). Therefore, it is important to inform the elderly population of the behavioral modifications benefits of the QOL.…”
mentioning
confidence: 74%
“…Factor 2, "not to respect to elderly patients' autonomy and privacy", consisted of three items (10,11,9); the minimum item/factor correlation was 0.513. Factor 3 "not to evaluate decision making competency", consisted of four items (1,3,15,7); the minimum item/ factor correlation was 0.537. Factor 4, "ignoring the individuality of elders", consisted of three items (6,5,8); the minimum item/factor correlation was 0.591.…”
Section: Resultsmentioning
confidence: 99%
“…According to some studies, life expectancy in Iran in 1986 was 66 and 69 for men and women, respectively (50), while in 1996 this index was 70.7 and 73.4 for men and women, respectively, indicating a 4.5% increase (51). According to WHO, in 2005, 6.4% of the Iranian population were over age 60, and it is predicted that 25.6% of both men and women will reach this age group in 2050; if other variables are kept constant, the per capita should be 2.5-fold until 2050 (52). Although an increased life expectancy is good news, it is usually associated with a reduction in physical and physiologic ability, as well as an increased risk for chronic mental and physical diseases.…”
Section: Discussionmentioning
confidence: 99%